Sobrepeso, obesidade e imc ajustado por diversos fatores na população de um município brasileiro em todas faixas etárias. - Lima, Raquel Patricia Ataíde (2012)
This study assessed the overweight, obesity and BMI - Body Mass Index prevalence adjusted for demographic, socioeconomic and lifestyle variables in all age groups. This is a cross-sectional population-based epidemiological study with stratified and systematic sampling involving 1165 individuals of all ages from the population of a city in northeastern Brazil, from July 2008 to January 2010. From visits to selected households, the following was performed: application of a demographic questionnaire, weight and height measurement, socioeconomic evaluation on family income and education level, practice of physical activities, alcohol consumption and smoking. When the common statistical model was applied, a relationship was observed between overweight and obesity prevalence and the following factors: age group and gender in the total sample and when distributed by age, educational level, in the total sample and when distributed by age group, income when distributed by age group based on the median income. As for lifestyle, only smoking was associated with overweight and obesity prevalence in adults and in the total sample. The following results were significant (p <0.05): age group from 20 to 59 years, when the individual had schooling greater than or equal to high school, the average BMI increased by 2.4760 kg/m2; age group ≥ 60 years, when the individual was female and BMI increased on average 1.7209 kg/m2. It is noteworthy that schooling and being female also stood out in the adjustment to total population as major factors influencing the increased BMI, followed by variables physical activity and family income. The adjusted results justify the adoption of intervention and prevention policies against these clinical conditions for the study population as a whole, specially directed to adults of higher education level, as well as for elderly females.